Genomic characterization of Staphylococcus aureus isolated from mastitis in small ruminants in Sardinia, Italy - Moawad, Amira A.; Dore, Simone; Lollai, Stefano; El-Adawy, Hosny; Brangsch, Hanka; Monecke, Stefan; Ehricht, Ralf; Braun, Sascha D.; Neubauer, Heinrich; Tomaso, Herbert (Frontiers in Microbiology, 2025)
BackgroundStaphylococcal mastitis is a common disease of small ruminants causing major economic losses. The problem is particularly significant in the rural areas of the Mediterranean region, where almost two thirds of the global sheep and a quarter of the global goat milk are produced. This study aimed to gain insight into the genotypes, antimicrobial resistance (AMR) profiles and virulence factors of Staphylococcus aureus isolated from clinical mastitis in small ruminants’ farms from different 25 dairy herds in six different provinces in Sardinia, Italy between December 2021 and May 2022.MethodsThirty- two S. aureus were phenotypically identified and confirmed by real-time PCR. Whole-genome sequencing (WGS) was conducted and the sequence data were analyzed to reveal the genetic diversity, AMR markers and virulence genes to draw a conclusion for a current situation of small ruminants’ clinical mastitis in dairy herds in the region and the potential public health risk. Furthermore, the phylogenetic relations between S. aureus strains within one farm and from various farms was analyzed.ResultsAll isolates proved to be phenotypically Methicillin-susceptible S. aureus (MSSA), and none of them harbored mecA/C genes. The antimicrobial resistance against Tetracycline and Erythromycin were 15.62% and 3.12%, respectively. The isolates were assigned to ten sequence types in addition to five different clonal complexes using multilocus sequence typing (MLST). Sequence types ST133 (46.9%) and ST700 (21.9%) were the dominant types, and the majority of isolates were assigned to either CC133 (56.25%) or CC130 (34.4%). Twelve different spa-types were identified among isolates, while six isolates were not assigned to known spa-types. The dominant spa-type was t1773 (18.75%) which is known to be associated with CC130. All Tetracycline-resistant isolates harbored tet genes. The only Erythromycin-resistant isolate carried the erm(T) gene. The leucocidin genes lukF-PV (P83)/lukM were detected in 20 isolates (62.5%), while one isolate (ST522) carried a chimeric leukocidin.ConclusionIn conclusion, this study showed a considerable genetic diversity of S. aureus isolated from sheep and goat mastitis in Sardinia, Italy, and the prominent sensitivity to most of antimicrobial agents relevant for mastitis treatment. These findings inform about the local mastitis control strategies and highlight a low immediate public health risk from antimicrobial resistance in this setting.